Lipopolysaccharide and tyloxapol accelerate the development of atherosclerosis in mice. Issue 2 (7th December 2021) - Jin, Meiyu; Zhang, Di; Zheng, Lianwen; Wei, Yunfei; Yan, Siru; Qin, Haiyan; Wang, Qi; Zhao, Lilei; Feng, Haihua
Abstract: The occurrence of atherosclerosis is closely related to inflammation and lipid metabolism disorder. It has been found that lipopolysaccharide (LPS) could induce inflammation, and tyloxapol (Ty) could induce hyperlipidemia. However, the effects of LPS and Ty on the development and mechanism of atherosclerosis have not been investigated thoroughly. To answer this question, we used assay kits to detect total cholesterol (TC), triglyceride (TG), and low‐density lipoprotein (LDL) content to evaluate dyslipidemia. We used hematoxylin and eosin staining to evaluate the pathological structure of the aorta and liver, and then used Oil Red O staining to access lipid accumulation in the aortic wall. Subsequently, we used the alanine transaminase (ALT) kit to examine the liver injury. Finally, we used the Western blot experiment to measure proteins that regulate lipid metabolism. We found that the LPS + Ty group could increase the levels of TC, TG, and LDL in the serum and promote lipid accumulation in the aortic wall in mice. Moreover, our study showed that the LPS + Ty group induced pathological changes in hepatocytes and increased ALT content in mice. Significantly, we found that the LPS + Ty group could activate acetyl‐CoA carboxylase, sterol regulatory element‐binding protein‐1c, and inhibit peroxisome proliferator‐activated receptors α in mice. Therefore, we suppose that LPS and Ty aggravated the development of atherosclerosis by promoting hyperlipidemia and the disorder of lipid metabolism in mice. These findings are significant for the study of the pathogenesis of atherosclerosis and the selection of animal models.